CFIN, 6th Edition - Scott Besley; Eugene Brigham (Cengage Learning, 2018)
Learn Corporate Finance YOUR Way with CFIN6! CFIN6's easy-reference textbook presents course content through visually engaging chapters as well as extensive end-of-chapter reviews that make this a ready-made study tool.